Does The Leader And Law Enforcement Impact Civil Servant Performance - Ahmadi, Rulam; Abdul Manap; Diana Pujiningsih; Asep Saepullah; Arief Yanto Rukmana (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
This study aims to investigate: 1) the impact of leadership, discipline, and work ethic on the performance of the State Civil Apparatus at the Livestock Service of East Java Province, 2) the impact of leadership, discipline, and work ethic on the performance of the State Civil Apparatus at the Livestock Service of East Java Province concurrently, and 3) the variables that most dominantly influence the performance of the State Civil Apparatus at the East Java Province. The research findings show that: 1) Leadership partially influences performance; 2) Work Discipline has no effect on performance; 3) The coefficient of determination results show that 88.5% of employee performance variables can be explained by independent variables, namely Leadership (X1) and Work Discipline (X2), while the remaining 13.7% is explained by other variables outside the study.